2008
DOI: 10.1103/physrevlett.101.135001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Dynamics Simulations of Electron-Ion Temperature Relaxation in a Classical Coulomb Plasma

Abstract: Molecular-dynamics simulations are used to investigate temperature relaxation between electrons and ions in a fully ionized, classical Coulomb plasma with minimal assumptions. Recombination is avoided by using like charges. The relaxation rate agrees with theory in the weak coupling limit (g identical with potential/kinetic energy << 1), whereas it saturates at g > 1 due to correlation effects. The "Coulomb log" is found to be independent of the ion charge (at constant g) and mass ratio > 25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
158
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(193 citation statements)
references
References 10 publications
16
158
1
Order By: Relevance
“…(dT e /dt = −dT i /dt) were noted in earlier work on hydrogen plasmas [8,9,[11][12][13]. In our cases here, however, the ions are sufficiently cold that such an asymmetric temperature relax-ation is expected [7,21,23].…”
Section: Resultsmentioning
confidence: 47%
See 4 more Smart Citations
“…(dT e /dt = −dT i /dt) were noted in earlier work on hydrogen plasmas [8,9,[11][12][13]. In our cases here, however, the ions are sufficiently cold that such an asymmetric temperature relax-ation is expected [7,21,23].…”
Section: Resultsmentioning
confidence: 47%
“…For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8]. Furthermore, it was shown that for many regimes of interest to ICF, the complex dynamical screening of the 2-component (electron + proton) plasma could be replaced by the static response of the electrons alone, yielding identical results [8,9,12,13]. This is hardly surprising, since in a given electronproton collision, the "spectator" electrons are expected to move much faster than the much heavier "spectator" protons.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations